Sacral erector spinae block: A new era for postoperative analgesia—a narrative review - Teena Bansal; Suresh Singhal (Journal of Anaesthesiology Clinical Pharmacology, 2025)
Erector spinae muscle extends throughout the cervical, thoracic, lumbar and sacral regions. Sacral erector spinae block is performed by depositing the local anaesthetic in the fascial plane deep to erector spinae muscle at sacral level. Local anaesthetic gets distributed in craniocaudal fascial plane and exerts its effect on ventral and dorsal rami of spinal nerves. Block at sacral level provides excellent postoperative analgesia. This block has been used as a sole anaesthetic technique as well. The rationale and focus of this narrative view are to provide an overview of the effectiveness and indications of sacral erector spinae block in addition to techniques used for this block. Sacral erector spinae block provides many advantages. It covers many dermatomes using longitudinal midline technique. It is safe as it is a superficial block. The block does not cause hypotension and bradycardia, hence there is no haemodynamic instability. The block is an excellent modality for postoperative analgesia, chronic pain relief as well as surgical anaesthesia. It works effectively for both children as well as adults and can prove a new era for postoperative analgesia in future.